2019
DOI: 10.1088/1742-6596/1315/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical learning by utilizing loce, manggaraian traditional mats

Abstract: This study discussed the exploration of mathematical concepts in Traditional Mat, Loce, as a product of Manggarai culture. This study aimed to describe the mathematical ideas contained in the Traditional Mat, Loce, Manggarai and how the linkages between the concepts found in the traditional mats, Loce, Manggarai and the topic of learning in schools. This research was qualitative research with ethnographic methods. Data collections were carried out through observation, interviews, and documentation. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There are several previous studies related to Mbaru Niang which show that there are fundamental mathematical activities found in the Mbaru Niang Traditional House, including counting, measuring, locating, designing, and explaining activities (Hanim et al, 2019;Wara et al, 2022). The research conducted is somewhat different because previous researchers focused more on fundamental mathematical activities while our research focused more on identifying cultural values contained in the Mbaru Niang to be implemented in learning.…”
Section: Mbaru Niangmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several previous studies related to Mbaru Niang which show that there are fundamental mathematical activities found in the Mbaru Niang Traditional House, including counting, measuring, locating, designing, and explaining activities (Hanim et al, 2019;Wara et al, 2022). The research conducted is somewhat different because previous researchers focused more on fundamental mathematical activities while our research focused more on identifying cultural values contained in the Mbaru Niang to be implemented in learning.…”
Section: Mbaru Niangmentioning
confidence: 99%
“…The research conducted is somewhat different because previous researchers focused more on fundamental mathematical activities while our research focused more on identifying cultural values contained in the Mbaru Niang to be implemented in learning. In addition, the results of research by Sukmadinanta & Alexon (2012) concluded that (1) students' appreciation of local culture increases if learning focuses on themes developed based on students' early cultural experiences; and (2) learning outcomes improve if teaching integrates culture Hanim, et al, 2019, show that the STAD cooperative learning model based on Minangkabau culture was proven to be able to improve student economic learning achievement. The results of these researchers illustrate the importance of culture-based learning in schools where children can learn from real experiences that are around them through certain cultures in the environment where they live.…”
Section: Mbaru Niangmentioning
confidence: 99%
“…Ethno mathematics in Indonesia is actually not a new science, but has been known since mathematics was introduced. It's just that this discipline was realized after some scientists introduced the name ethno mathematics as part of the science of mathematics (Hanim et al, 2019). Therefore, there are now many developments in ethno mathematics, especially in learning applications in schools.…”
Section: Introductionmentioning
confidence: 99%